Living (stained) calcareous benthic foraminiferal assemblages (>125 μm) in a coastal upwelling zone of the Humboldt Current System, Northern Chile(∼27°S) - Castillo, Alexis; Hromic, Tatiana; Uribe, Roberto A.; Valdes, Jorge; Sifeddine, Abdel; Quezada, Lyta; Vega, Sue-Ellen; Arencibia, Ariel; Diaz Ochoa, Javier Augusto; Guinez, Marcos (My University, 2021)
In coastal upwelling ecosystems, understanding of environmental factors regulating the structure of benthic foraminiferal communities is fundamental to enhance our knowledge of their ecology and to validate their use in palaeoceanographic studies. In this study, we assess the influence of organic matter (quantity/quality) and subsurface oxygenation on living (stained) calcareous benthic foraminifera inhabiting a coastal upwelling ecosystem influenced by Oxygen Minimum Zone (OMZ) off Inglesa Bay, Northern Chile. Benthic foraminifera and their environment (i.e. biochemical/elemental sediment composition and subsurface water column oxygenation) were sampled along a transect perpendicular to the coastline consisting of three stations (30, 70 and 120 m) and covering two seasons (winter and summer). The geochemical composition of surface sediments and subsurface oxygenation reveal a typical pattern of marine ecosystems associated with coastal upwelling centers influenced by OMZ. Forty-seven species of living calcareous benthic foraminifera were identified, in which Bolivinella seminuda, Buliminella elegantissima, Bulimina marginata, and Nonionella miocenica were found as the most abundant species. Total abundance increases remarkably with depth while taxonomic richness and evenness decrease. Multivariate analyses show three benthic foraminiferal associations strongly linked to nutritive organic matter and subsurface oxygenation, regardless of the sampling period. Assemblages "A'(22 species, 4 dominant) and "C"(5 species, 1 dominant) are associated with the shallow (30 m) and deep (120 m) station, and present contrasting subsurface oxygenation and organic matter content. Assemblage "B"(19 species, 3 dominant) is associated with the intermediate station (70 m) characterized by mixed subsurface oxygenation and organic matter content. Our results suggest that local environment conditions (i.e. OMZ intensity, organic matter quality/quantity) govern the structure and composition of the living calcareous benthic foraminiferal assemblages of Inglesa Bay. Such assemblages have similarities and differences with other benthic foraminifera assemblages found in other coastal upwelling ecosystems impinged by an OMZ. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: oxygen minimum zone; calcareous benthic foraminifera; humboldt current system; inglesa bay; permanova; biochemical components